THE INFLUENCE OF LEARNING ENVIRONMENT AND LEARNING MOTIVATION ON STUDENTS' PAI LEARNING OUTCOMES AT SMP BINA SATRIA - Pratama, M Siddik (Universitas Dharmawangsa, 2022)
Based on the results of the research analysis, it can be concluded: (1) After the partial t-test, it got a sig value of 0.001 <0.05 so that there is a positive and significant influence between the learning environment and PAI learning outcomes, (2) After the partial t-test, it got a sig value of 0.001 < 0.05 so that there is a positive and significant influence between learning motivation and PAI learning outcomes, (3) after the simultaneous f-test, it got a sig value of 0.001 < 0.05 so that simultaneously there is a positive and significant influence between the learning environment and learning motivation on PAI learning outcomes of students at SMP Bina Satria, the magnitude of the influence of the learning environment and learning motivation is 72.4% and the rest is influenced by other factors,